Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. The effect of jobs on the forms of the villages of Taif GovernorateDr. Maleeha Hamed Alabdali2. The Culture of Swapping Children’s Clothes Between Mothers in Saudi Arabia and its Relationship to Sustainability in Consumer BehaviorMrs. Aroub Abdullah Qasti, Prof. Maha Abdullah Al-Dabbagh3. The impact of opportunity sales (discounts) on Impulse purchase for clothes in the Saudi society and measuring the community's awareness of the negative repercussions of Impulse purchase on the environmentMrs. Ihsan Ayed Al-Ahmari, Prof. Maha Abdullah Al-Dabbagh4. Changes in Online Shopping Behavior for Ready-Made Clothes among Saudi Consumers following COVID-19Mrs. Areej Saleh Al-Zahrani, Prof. Maha Abdullah Al-Dabbagh5. The impact of advertising on the circular economy of fashion on consumers' acceptance of reused and recycled fashionMrs. Suad Abdullah Al-Ghamdi, Prof. Maha Abdullah Al-Dabbagh6. Exploring the Influence of Ethical Consumption on Sustainable Fashion Choices in Saudi ArabiaMrs. Sally Majid Thabet Muhammad, Prof. Maha Abdullah Al-Dabbagh
Keywords: Journal of Human And Social Sciences